STUDENT LEARNING OUTCOMES ON THE APPLICATION OF TGT LEARNING MODEL THROUGH DEVELOPMENT MEDIA SNAKES LADDERS - Khairi, Miftahul (INCARE, International Journal of Educational Resources, 2023)
This research is motivated by the low learning outcomes of students caused by several factors, such as the use of learning models and the development of learning media that are appropriate and in accordance with the needs of students. This study aims to determine differences in student learning outcomes through the application of the Teams Games Tournament (TGT) learning model through the development of snakes and ladders media on fractional arithmetic operations. The method used is a form of true experimental research with a posttest only control design . This research was conducted in two classes, namely Class VB as an Experimental class with a total of 15 students and Class VA as a control class with a total of 29 students. This research instrument uses student learning outcomes tests. Data analysis to determine differences in learning outcomes using t-test statistics. The results showed that the average post-test score for the experimental class was 86.5 and the control class average was 72.9, and the combined standard deviation was 12.96. Then the calculated t is 2.918 and we get t table = 2.056. Thus t count > t table. It was concluded that there were differences in student learning outcomes on fractional arithmetic operations material by applying the Teams Games Tournament (TGT) learning model through the development of snakes and ladders media which was better than student learning outcomes on fractional arithmetic operations material by applying conventional learning models without using media.